Uncertainty and the Cost of Bank vs. Bond Finance - Christian Grimme (Center for Economic Studies and ifo Institute (CESifo), 2019)
How does uncertainty affect the costs of raising finance in the bond market and via bank loans? Empirically, this paper finds that heightened uncertainty is accompanied by an increase in corporate bond yields and a decrease in bank lending rates. This finding can be explained with a model that includes costly state verification and a special informational role for banks. To reduce uncertainty, banks acquire additional costly information about borrowers. More information increases the value of the lending relationship and lowers the lending rate. Bond investors demand compensation for the increased risk of firm default.
Keywords: E32; E43; E44; G21; 330; uncertainty shocks; financial frictions; relationship banking; bank loan rate setting; information acquisition